1996
DOI: 10.1111/j.1651-2227.1996.tb13999.x
|View full text |Cite
|
Sign up to set email alerts
|

Early diet of preterm infants and bone mineralization at age five years

Abstract: Bone disease with significantly reduced bone mineralization is common in preterm infants, and associated with later linear growth stunting at 18 months of age. Dietary insufficiency of calcium and phosphorus is thought to be the principal aetiological factor. We studied 54 children at mean age 5 years who were born preterm and had participated in a prospective multicentre study of effects of early diet on later growth and development. Diets compared were banked donor breast milk and preterm formula fed as a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
2
7

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 28 publications
2
76
2
7
Order By: Relevance
“…In humans, this appears to be the case for ischaemic heart disease, diabetes mellitus and hypertension (Barker, 1993). It appears likely to apply to bone also as we, and others, have previously reported early life associations with smoking in utero and breast-feeding in early life (Jones et al, 2000a,b;Backstrom et al, 1999) as well as breast milk supplementation, although the bene®t reported at age 5 y did not persist at age 11 y (Bishop et al, 1996;Fewtrell et al, 1999). The dietary associations we report in this paper are independent of these factors and, unlike both breast-feeding and smoking, are present in both term and preterm infants, suggesting that they are not dependent on a possible physiology of maturity.…”
Section: Discussionmentioning
confidence: 61%
“…In humans, this appears to be the case for ischaemic heart disease, diabetes mellitus and hypertension (Barker, 1993). It appears likely to apply to bone also as we, and others, have previously reported early life associations with smoking in utero and breast-feeding in early life (Jones et al, 2000a,b;Backstrom et al, 1999) as well as breast milk supplementation, although the bene®t reported at age 5 y did not persist at age 11 y (Bishop et al, 1996;Fewtrell et al, 1999). The dietary associations we report in this paper are independent of these factors and, unlike both breast-feeding and smoking, are present in both term and preterm infants, suggesting that they are not dependent on a possible physiology of maturity.…”
Section: Discussionmentioning
confidence: 61%
“…During the first year of life, several investigators report that the forearm bone mass of preterm infants is lower than that of term infants, 2,17,18 but the preterm child may resolve this difference in bone mineralization by 2 years of age. [18][19][20] However, another study of adolescents with a mean age of 15 years who were born at extremely low birth weight <1000 g reports significantly lower total body mineral content but not density compared with control adolescents. 13 Total bone mineral content is the measurement of the weight of hydroxapatite or calcium whereas bone density is the bone mineral content divided by the area.…”
Section: Discussionmentioning
confidence: 96%
“…Resultados de estudos recentes sobre consumo de cálcio na alimentação indicam que a ingestão de quantidades adequadas de cálcio na dieta contribui à manutenção da pressão sangüínea em níveis ótimos (BISHOP et al, 1996;GERRIOR et al, 1998).…”
Section: 1papel Do Cálcio Na Manutenção Da Saúde Humanaunclassified
“…Tal processo engloba a degradação e reabsorção de massa óssea existente e posterior deposição de novo material ósseo. A formação de massa óssea excede a reabsorção durante o período de crescimento, ou seja, durante a infância e juventude, estabilizando-se durante a fase adulta (BISHOP et al, 1996;GERRIOR et al, 1998).…”
Section: 1papel Do Cálcio Na Manutenção Da Saúde Humanaunclassified
See 1 more Smart Citation